2017
DOI: 10.1530/jme-16-0171
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and functional analysis of Ctrp9 in Epinephelus coioides

Abstract: CTRP9 is a member of the C1q/TNF-related protein (CTRP) superfamily and has been studied in mammals, whereas the comparative studies of CTRP9 in non-mammalian species are still absent. In this study, was isolated and characterized from the orange-spotted grouper (). The full-length cDNA of was 1378 bp in size with an ORF (open reading frame) of 1020 bp that encodes a 339 amino acid pre-pro hormone. The mRNA expression of showed a rather high level in the kidney and brain, but a low level in other tissues. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Similarly, mouse CTRP9 and human CTRP9 share 84% amino acid identity as well. CTRP9 mainly expresses in adipose tissue, adipocytes and adipose stromal cells and is detectable in variety of tissues and organs, such as skeletal muscle, brain, liver, and kidney (Li, Zhu et al, ; Yang et al, ). It is noteworthy that only human and primates (chimpanzee and rhesus macaque) possess the CTRP9B so far, even though at extremely low expression levels (Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mouse CTRP9 and human CTRP9 share 84% amino acid identity as well. CTRP9 mainly expresses in adipose tissue, adipocytes and adipose stromal cells and is detectable in variety of tissues and organs, such as skeletal muscle, brain, liver, and kidney (Li, Zhu et al, ; Yang et al, ). It is noteworthy that only human and primates (chimpanzee and rhesus macaque) possess the CTRP9B so far, even though at extremely low expression levels (Peterson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study indicated that MSC proliferation and viability, immune modulation, and angiogenesis-related paracrine ability were all impaired in MSCs from aged donors. CTRP9 is a novel adipokine exclusively expressed in adipocytes and also highly expressed in the brain (10). CTRP9 has been suggested to act as a regulator of vascular function, and to exert protective effects in ischemic diseases (12).…”
Section: Discussionmentioning
confidence: 99%
“…AmongC1q and tumor necrosis factor-related protein (CTRP) family members, CTRP9 displays the highest amino acid identity to APN. CRTP9 is also highly expressed in brain tissue (10), and acts as an adipocytokine with beneficial effects on glucose metabolism, cellular survival, oxidant response regulation, and inhibition of endoplasmic reticulum stress, all of which are related to the cellular senescence process (11)(12)(13). However, the effect of exogenous CTRP9 on cellular senescence in MSCs, which adversely affects the function of engrafted stem cells, has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…and , respectively,) from the tongue sole. Recombinant tongue sole IGF‐1 and IGF‐2 proteins were obtained from P. pastoris as described previously (Li et al., ; Yang et al., ) with some modifications. Briefly, the cDNA fragments encoding tongue sole mature IGF‐2 were cloned by PCR with specific primers (Forward primer P1: 5′ CTCGAGAAAAGAGAGGCTGAAGCTGA AATGGCCT 3′; Reverse primer P2: 5′ TCTAGACTAATGATGATGATGATGATGCGTGGAC TTGGG 3′).…”
Section: Methodsmentioning
confidence: 99%
“…As for the existing expression systems, the protein expressed from a prokaryotic system is always an insoluble inclusion body and requires denaturation and renaturation before it has active bioactivity, which is inefficient and uneconomical for large‐scale production (Sahdev, Khattar, & Saini, ). In recent years, the production of recombinant proteins has increasingly focused on yeast (Chen et al., ; Li et al., ; Sanchis‐Benlloch et al., ; Yang et al., ). Pichia pastoris ( P. pastoris ) is a methylotrophic yeast belonging to the Ascomycetes group.…”
Section: Introductionmentioning
confidence: 99%